2002
DOI: 10.1093/carcin/23.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of repair of ultraviolet damage in the host-cell reactivation assay by polymorphic XPC and XPD/ERCC2 genotypes

Abstract: DNA repair capacity (DRC) plays an important role in genetic susceptibility to cancer. Polymorphisms of a number of DNA repair genes involved in several distinct pathways have been identified. However, their effects on repair function have not been well characterized. We demonstrated previously that DRC for removal of benzo[a]pyrene diol epoxide-induced DNA damage measured by a host-cell reactivation assay was modulated by two XPD/ERCC2 polymorphisms in lung cancer. In this report, we investigated the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
136
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(159 citation statements)
references
References 26 publications
17
136
1
5
Order By: Relevance
“…These results suggest that the -371A allele has a recessive effect on the XPC phenotype, as is the case of the XPD Asp312Asn (23592G?A of exon 10) polymorphism. 28,29 In the current study, we also found that the -27G?C polymorphism was associated with a significantly increased risk of overall lung cancer. The risk effect of the -27C allele was statistically significant only for SM, though observed for the 3 major histologic types of lung cancer.…”
Section: Discussionsupporting
confidence: 66%
“…These results suggest that the -371A allele has a recessive effect on the XPC phenotype, as is the case of the XPD Asp312Asn (23592G?A of exon 10) polymorphism. 28,29 In the current study, we also found that the -27G?C polymorphism was associated with a significantly increased risk of overall lung cancer. The risk effect of the -27C allele was statistically significant only for SM, though observed for the 3 major histologic types of lung cancer.…”
Section: Discussionsupporting
confidence: 66%
“…It is likely that altered XPD activity is caused by the variant allele, although its functional impact remains controversial [18]. A previous study by Qiao et al showed that the variant allele of XPD (K751Q) polymorphism was associated with lower DNA repair capacity than the common allele [19]. However, our earlier study indicated that the variant allele genotype for this polymorphism was associated with increased repair of chromosomal aberrations and lower micronuclei formation [20,21].…”
Section: Discussionmentioning
confidence: 74%
“…These two polymorphisms in XPC and XPD have also been found to interact to modify risk of lung cancer [25]. The K939Q polymorphism of XPC alters the function of XPC protein [19] and dysfunctional XPC has been reported to cause growth arrest in cells which might constitute a barrier against cancer development and progression [26]. Previously we reported a positive association of XPC (K939Q) polymorphism with risk of urinary bladder cancer and no association for breast cancer [9,27].…”
Section: Discussionmentioning
confidence: 97%
“…These two polymorphisms involve changes in protein sequence [22,24] and have been associated with the risk of developing several cancers [25][26][27]. Moreover, experimental data [28,29] suggest that both the TA and the CC haplotypes result in protein variants that are less active in DNA repair than the CA wild-type. We found that the CA wild-type haplotype was associated with a favorable response to imatinib, as patients who carried one or two copies of such haplotype had a fourfold lower risk of achieving suboptimal response or failure to imatinib than the remainders.…”
Section: Discussionmentioning
confidence: 99%